Calculating the thermal conductivity of the silicon clathrates using the quasi‐harmonic approximation. Issue 3 (30th November 2015) - Madsen, Georg K. H.; Katre, Ankita; Bera, Chandan
Abstract : A model of the lattice thermal conductivity, based on the quasi‐harmonic approximation, is validated on a dataset of 42 rock‐salt and zinc‐blende compounds. The model reliably reproduces experimental thermal conductivities ranging over several orders of magnitude. The good performance of the model is related to the definition of the mode‐averaged Grüneisen parameter. The model is applied to the silicon‐based clathrates and found to correctly reproduce the two orders of magnitude reduction of the lattice thermal conductivity compared to Silicon in the diamond structure. It is shown how the introduction of the clathrate structure and the guest atoms lead to a reduction of approximately one order of magnitude each. The clathrate structure is found to both increase the anharmonicity and decrease the average phonon velocity, whereas the reduction due to the guest atom is almost purely due to increased anharmonicity.